ANDES: The first system for flash flood monitoring and forecasting in Peru - Lavado-Casimiro, W. (2020)
Hydrological hazards related to flash floods (FF) in Peru have caused many economic and human life losses in recent years. In this context, developing complete early warning systems against FF is necessary to cope impacts. For this purpose, hydrological and hydraulic models coupled to numerical weather models (NWM) that provide forecasts are generally used. In this sense, the National Meteorological and Hydrological Service of Peru (SENAMHI) has launched the ANDES initiative (Operational Forecasting System for Flash Floods of SENAMHI in English) to support FF events.